2014
DOI: 10.1021/ac5030914
|View full text |Cite
|
Sign up to set email alerts
|

Correlated Imaging with C60-SIMS and Confocal Raman Microscopy: Visualization of Cell-Scale Molecular Distributions in Bacterial Biofilms

Abstract: Secondary ion mass spectrometry (SIMS) and confocal Raman microscopy (CRM) are combined to analyze the chemical composition of cultured Pseudomonas aeruginosa biofilms, providing complementary chemical information for multiple analytes within the sample. Precise spatial correlation between SIMS and CRM images is achieved by applying a chemical microdroplet array to the sample surface which is used to navigate the sample, relocate regions of interest, and align image data. CRM is then employed to nondestructive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 39 publications
(63 reference statements)
1
68
0
Order By: Relevance
“…Manually probing the cells with SIMS revealed that the 7-h biofilm mass spectrum exhibits prominent peaks at m/z 244.18, 260.18, 270.20, 272.21, 286.19, 288.21, and 298.23, which have been previously assigned to 2-alkyl-4-(1H) quinolines (AQ) MH + ions and are confirmed here with tandem MS (Table 1 and Figure S1, Supplemental Information). 10,23,24 The observed ions fall into three molecular classes, specifically 2-heptyl-4-quinoline (HHQ)-derived ( m/z 244.18, 270.20, and 272.21), 2-heptyl-3-hydroxyquinolone (PQS)-derived ( m/z 260.18 and 288.21), and 4-hydroxy-2-heptylquinoline-N-oxide (HQNO)-derived ( m/z 260.18, 286.19 and 288.21) ions. Among these compounds, the isomeric pairs PQS/HQNO and C 9 -PQS/NQNO both appear in the 7-h biofilm based upon tandem-MS fragmentation patterns (Figure S1, Supplemental Information).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Manually probing the cells with SIMS revealed that the 7-h biofilm mass spectrum exhibits prominent peaks at m/z 244.18, 260.18, 270.20, 272.21, 286.19, 288.21, and 298.23, which have been previously assigned to 2-alkyl-4-(1H) quinolines (AQ) MH + ions and are confirmed here with tandem MS (Table 1 and Figure S1, Supplemental Information). 10,23,24 The observed ions fall into three molecular classes, specifically 2-heptyl-4-quinoline (HHQ)-derived ( m/z 244.18, 270.20, and 272.21), 2-heptyl-3-hydroxyquinolone (PQS)-derived ( m/z 260.18 and 288.21), and 4-hydroxy-2-heptylquinoline-N-oxide (HQNO)-derived ( m/z 260.18, 286.19 and 288.21) ions. Among these compounds, the isomeric pairs PQS/HQNO and C 9 -PQS/NQNO both appear in the 7-h biofilm based upon tandem-MS fragmentation patterns (Figure S1, Supplemental Information).…”
Section: Resultsmentioning
confidence: 99%
“…10 P. aeruginosa is an opportunistic pathogen for both plants and humans and is responsible for approximately 8% of the healthcare associated infections each year. 11 Among the commonly infected are burn victims and the immuno-compromised, such as cystic fibrosis patients.…”
Section: Introductionmentioning
confidence: 99%
“…MALDI-MS was used to obtain chemical information about rhamnolipid species; nine different species were found. In another study, the same group showed the presence of quinolone signaling molecules in Pseudomonas aeruginosa biofilms using Raman spectroscopy for the first time and analyzed the distribution of quinolone species with secondary ion mass spectrometry (SIMS) [44].…”
Section: Raman Spectroscopy Of Biofilmsmentioning
confidence: 99%
“…157 The necrotic core of the spheroids experienced greater Raman variability and correlated with the principal component causing the greatest variance in the data. 157 Additionally, CRM was also correlated with C60-SIMS to show consistent distribution of quinolone disruptions between the new analytical techniques, with specific molecular identities determined through tandem MS. 198 …”
Section: Multimodal Imaging Systemsmentioning
confidence: 99%